Association Between Systemic and Local Oxidative Stress of Infertile Women Undergoing Ivf/Icsi - Mahdi, Qais Ahmed; Abdul Wadood, Shatha; Hamza, Rusul H (Iraqi Journal of Science, 2019)
Oxidative stress (OS) may affect in vitro fertilization (IVF) outcomes in infertile women undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). The aim of this study is to explore the possible relationships between OS parameters in serum and follicular fluid (FF) from infertile women with male cause infertility (n=40), women with polycystic ovary syndrome (PCOS) (n=40), and women with unexplained infertility (UI)(n=45) undergoing IVF/ICSI. The collection of blood and FF samples was done at the day of oocyte aspiration. Total peroxide (TPX) level, total antioxidant capacity (TAC), and malondialdehyde (MDA) level were measured in serum and FF; whereas, glutathione-s-transferase (GST) activity and superoxide dismutase (SOD) activity were measured in FF. Also, oxidative stress index (OSI) that is the percentage ratio of TPX to TAC, was calculated. In the control group, correlation analysis reveals the presence of a significant positive association between FF OSI with serum OSI, FF TPX with FF OSI, and serum TPX with FF GST activity. In the PCOS group, there was a significant negative association between: FF TPX and serum TAC level. However, non-significant relationship was found between serum and FF OS status parameters in the UI group. It’s concluded from the present study that systemic OS may give valuable information about local OS occurrence (blood OS reflects FF OS) only in control group and PCOS group. Such information could be useful for a better understanding of the pathological OS mechanisms involved in IVF failure for patients with different causes of infertility.